Two new species and three new records of Diachea (Physarales) from China based on morphological and molecular evidence - Li, Xuefei; Dai, Dan; Tuo, Yonglan; Li, You; Hu, Jiajun; Sossah, Frederick Leo; Zhang, Bo; Li, Xiao; Li, Yu (Frontiers in Microbiology, 2024)
Diachea is an important genus of myxomycetes, recognized for its ecological role and wide distribution. This study aimed to expand knowledge of species diversity within this genus in China. We collected Diachea specimens from various locations in Shaanxi and Sichuan provinces and characterized them through morphological analysis and phylogenetic analysis using four genetic markers: small subunit ribosomal RNA (nSSU), translation elongation factor 1-alpha (EF-1α), mitochondrial small subunit (mtSSU), and alpha-tubulin gene (α-Tub). Based on these analyses, we describe two new species, namely, Diachea plectophylla and D. sichuanensis, discovered in the Shaanxi and Sichuan provinces, respectively. Diachea plectophylla is distinguished by its dense, rigid capillitium, spore warts, and distinct separation of capillitium ends from the peridium. Diachea sichuanensis, closely related to D. leucopodia, is identified by its blunt-headed columella, clustered spore warts, and robust stalks. In addition to these new species, we recorded five previously documented species, including D. bulbillosa in Gansu province, D. leucopodia in Yunnan and Sichuan provinces, and D. subsessilis in Sichuan province. Detailed descriptions, micrographs, taxonomic comparisons, and an identification key are provided to aid in accurate identification. The discovery of these new species not only enhances the known diversity of slime molds in the region but also provides valuable information for future studies on their geographical distribution and ecological relationships.